2018
DOI: 10.1098/rsob.170206
|View full text |Cite
|
Sign up to set email alerts
|

Deleting the IF 1 -like ζ subunit from Paracoccus denitrificans ATP synthase is not sufficient to activate ATP hydrolysis

Abstract: In oxidative phosphorylation, ATP synthases interconvert two forms of free energy: they are driven by the proton-motive force across an energy-transducing membrane to synthesize ATP and displace the ADP/ATP ratio from equilibrium. For thermodynamically efficient energy conversion they must be reversible catalysts. However, in many species ATP synthases are unidirectional catalysts (their rates of ATP hydrolysis are negligible), and in others mechanisms have evolved to regulate or minimize hydrolysis. Unidirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…Apparent K m values for ADP and phosphate were 11 µM and 104 µM, respectively. Under fully saturating conditions using 50 μM ADP and 10 mM phosphate, a maximal ATP synthesis rate of ~250 ± 50 nmol ATP min −1 mg −1 was obtained at 25 °C, which is in good accordance to a recent report for E. coli IMVs 7 . At maximal tested ADP (5 mM) and P i (100 mM) concentrations, the ATP synthesis rate declined to ~70%.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Apparent K m values for ADP and phosphate were 11 µM and 104 µM, respectively. Under fully saturating conditions using 50 μM ADP and 10 mM phosphate, a maximal ATP synthesis rate of ~250 ± 50 nmol ATP min −1 mg −1 was obtained at 25 °C, which is in good accordance to a recent report for E. coli IMVs 7 . At maximal tested ADP (5 mM) and P i (100 mM) concentrations, the ATP synthesis rate declined to ~70%.…”
Section: Resultssupporting
confidence: 91%
“…In order to minimize wasteful ATP hydrolysis, organisms have evolved different regulatory mechanisms, such as the inhibitory proteins IF1 in mitochondria 5,6 . A similar function has been attributed to the ζ subunit of the F 1 F 0 ATP synthase of Paracoccus denitrificans , but is currently debated 7 . In other bacteria such as B acillus PS3 and E. coli , the ε subunit has been proposed to ratchet the rotor in the synthesis direction 8 by extending its C-terminal domain along the γ subunit 912 , a conformational change that might be controlled by ATP binding in some bacteria 13 .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…IF1 knock down in HeLa cells [80] equipped with a FRET sensor for measuring the intracellular ATP concentration, surprisingly, did not affect cell viability or mitochondrial morphology, even though the cellular ATP concentration decreased by about a third. Moreover, recently it was reported that deleting the IF1-like ζ subunit from Paracoccus denitrificans has little influence on ATP hydrolysis by ATP synthase [81], confirming that the inhibition of the hydrolysis of ATP by uncoupled ATP synthase does not depend only on IF1 and that the subject requires further investigations. Also, in bacteria, when the concentration of the ATP reaches the physiological value, the ɛ subunit inhibits ATP synthase by binding to the c ring, and it has been proposed as a target for the design of anti-tuberculosis drugs [82].…”
Section: Inhibition Of Atp Hydrolysis: An Open Topicmentioning
confidence: 93%
“…The inhibited state of Ct-F 1 in these structures is likely due to unusual occupancy of the ‘open’ β by ADP (no Mg2+) and Pi. This inhibited state may be distinct from the MgADP-inhibited state trapped by azide in several structures of Mi-F 1 [116], as the Ct-F 1 structures occupy a significantly different rotary position than azide-inhibited Mi-F 1 (11° difference, as aligned by the γ-core). Also, although not observed yet structurally, Ct-F 1 can enter a state inhibited by the εCTD, as demonstrated earlier [50].…”
Section: Structural States Of ε In Bacterial Atp Synthases and Thementioning
confidence: 99%